The integration of online educational technologies and convergence among modalities at UFSM - Mallmann, Elena Maria; Bastos, Fábio da Purificação de; Dalmolin, Ricardo Simão Diniz (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
The aim is to critically analyze the actions carried out under the Center for Educational Technologies to induce integration of network technologies and convergence between modalities at the Federal University of Santa Maria (UFSM). Methodologically contemplate the policies and logistics research, development and training made possible by: 1) structuring multidisciplinary team focused on Virtual Environments for Teaching - Learning, Educational Resources and Activities Study, 2) conducting contests for professors in multidisciplinary area in eight different units of the UFSM, and 3) institutionalization of Moodle as Support for Classroom teaching in Undergraduate, Graduate and Extension courses, 4) interface academic between technologies Teacher Portal, Student Portal and Moodle, 5) selection of research projects for the Integration of Information and Communication Technology (ICT) and convergence of modalities in Undergraduate Education (public Notice no. 07/2012). Analytically, the approach includes unifiers parameters for all actions mentioned: a) presentation b) limit situation c) viable - possible. Conclusively, we signaled that the integration of network technologies and convergence between modes is a prospecting policy, viable - possible and innovative - sustainable, to reach the expansion and to enhance internalization of free public higher education